Building an Academic Colorectal Division - Koltun, Walter A. (Clinics in Colon and Rectal Surgery, 2014)
Colon and rectal surgery is fully justified as a valid subspecialty within academic university health centers, but such formal recognition at the organizational level is not the norm. Creating a colon and rectal division within a greater department of surgery requires an unfailing commitment to academic concepts while promulgating the improvements that come in patient care, research, and teaching from a specialty service perspective. The creation of divisional identity then opens the door for a strategic process that will grow the division even more as well as provide benefits to the institution within which it resides. The fundamentals of core values, academic commitment, and shared success reinforced by receptive leadership are critical. Attention to culture, commitment, collaboration, control, cost, and compensation leads to a successful academic division of colon and rectal surgery.
Keywords: core values; academic; research; division